Inter‐ and intraspecific spatial distributions, spatial segregation by dominants and emergent neutrality in understorey plants. Issue 10 (25th August 2021) - Ulrich, Werner; Olszewski, Piotr; Puchałka, Radosław; Sewerniak, Piotr; Koprowski, Marcin
Abstract : Tradeoffs between intra and interspecific distances of individual plants determine the spatial distributions of local plant communities and small‐scale community assembly. Here we use an individual based approach and null model standardization to compare intra‐ and interspecific nearest neighbour distances of plant ramets as well as mean differences in functional trait expression to nearest heterospecifics within local communities of temperate forest understorey plants in northern Poland. We found a general tendency towards clustered intraspecific and segregated interspecific ramet distributions. Spatial distribution patterns of understorey plants differed considerably between two nearby forest sites that mainly differed in the age structure of trees. Individuals of clonal species tended to have significantly smaller intraspecific and larger interspecific nearest neighbour distances than seed dispersing species. Our results indicate a major influence of dominant plant species on the spatial distributions of subdominants. Trait expressions related to plant growth (specific leaf area and leaf mass) and reproduction (seed mass) were significantly segregated in comparison to the spatial distribution of conspecific individuals and less so in comparison to heterospecific individuals. We argue that spatially explicit analyses of plant community assembly need to consider respective distributions of important traits and that the tradeoffs of contrasting trait distributions trigger small scale plant community composition and species distributions. We present a general framework for the analysis of plant community assembly based on the spatial distributions of individual plants and functional traits.